Pengaruh Harga, Daya Tarik Promosi dan Kualitas Produk Terhadap Keputusan Pembelian Pada Produk Kosmetik Emina (Studi Mahasiswi Manajemen Universitas Islam Malang Angkatan 2018) - Lia Tiana; Budi Wahono; Etty Saraswati (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThe study is aimed at understanding the impact of prices, the appeal of promotion and the quality of products on the decision of purchase on emina cosmetic products (class of poor, class of 2018), both partial and simultaneous. The research method used in this study is the quantitative method. The data used in this study are the primary data. The sample in this study represents 75 individuals from a total population of 298 management students with sampling samples taken. Hypothetical testing in this study using linear berganda regression. Research shows that price variables, promotional attractiveness and product quality are partial to purchase decisions. Price variables, the appeal of promotion and product quality simultaneously have significant impact on purchasing decisions. Keywords : Price, Promotional Appeal, Quality Of Product And Purchase Decisions.